Natural Polymers for Organ 3D Bioprinting - Liu, Fan (Polymers (Basel), 2018)
Three-dimensional (3D) bioprinting, known as a promising technology for bioartificial organ manufacturing, has provided unprecedented versatility to manipulate cells and other biomaterials with precise control their locations in space. Over the last decade, a number of 3D bioprinting technologies have been explored. Natural polymers have played a central role in supporting the cellular and biomolecular activities before, during and after the 3D bioprinting processes. These polymers have been widely used as effective cell-loading hydrogels for homogeneous/heterogeneous tissue/organ formation, hierarchical vascular/neural/lymphatic network construction, as well as multiple biological/biochemial/physiological/biomedical/pathological functionality realization. This review aims to cover recent progress in natural polymers for bioartificial organ 3D bioprinting. It is structured as introducing the important properties of 3D printable natural polymers, successful models of 3D tissue/organ construction and typical technologies for bioartificial organ 3D bioprinting.